2023
DOI: 10.1371/journal.pgph.0000636
|View full text |Cite
|
Sign up to set email alerts
|

“I know why I am taking this pill”: Young women navigation of disclosure and support for PrEP uptake and adherence in Eastern Cape Province, South Africa

Abstract: There is limited understanding of the dynamic interplay between adolescent girl’s and young women’s (AGYW) disclosure and social support for using oral pre-exposure prophylaxis (PrEP) and adherence. Towards this, we conducted interviews with 42 AGYW enrolled in The Community PrEP Study who exhibited either high or low blood concentrations of tenofovir-diphosphate (TFV-DP) in dried blood spots. Guided by Theories of Practice, interviews and analysis focused on AGYW perspectives and experiences with PrEP disclos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…This is consistent with other PrEP studies in South Africa which reported that women who disclosed to supportive social networks had better adherence (Giovenco et al, 2021 ; O’Rourke et al, 2021 ; Stoner et al, 2021 ; Straten et al, 2014 ). We have previously reported on the role of engaging families during home visits prior to PrEP initiation as a helpful component for building family support (Medina-Marino et al, 2021a ) and the importance of disclosure for improving PrEP adherence (Daniels et al, 2021c ). Our present analysis further confirms the need for engagement with family members and social support networks from an early stage in PrEP interventions for AGYW.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with other PrEP studies in South Africa which reported that women who disclosed to supportive social networks had better adherence (Giovenco et al, 2021 ; O’Rourke et al, 2021 ; Stoner et al, 2021 ; Straten et al, 2014 ). We have previously reported on the role of engaging families during home visits prior to PrEP initiation as a helpful component for building family support (Medina-Marino et al, 2021a ) and the importance of disclosure for improving PrEP adherence (Daniels et al, 2021c ). Our present analysis further confirms the need for engagement with family members and social support networks from an early stage in PrEP interventions for AGYW.…”
Section: Discussionmentioning
confidence: 99%
“…Together, routine disruptions and behaviour scrutiny from family, partners and friends, as well as HIV and sexual behaviour‐related stigma, negatively influenced AGYW self‐agency and ability to establish the habits needed for prevention‐effective use of PrEP [ 23 , 27 , 36 , 52 ]. Our work reveals the crucial role of supportive social networks for sustained PrEP use, including encouragement and pill reminders [ 37 ]. Given the importance of social acceptance among AGYW, peer and family‐based initiatives could prove critical for AGYW's decision to re‐initiate PrEP following breaks in use [ 11 , 21 , 36 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current behavioural intervention delivered by lay‐health counsellors as either a group‐based or one‐on‐one programme, included adherence support counselling and the development of action plans for problem‐solving. Adherence was measured using TFV‐DP concentrations in DBS samples, defining high and low adherence as ≥700 versus ≤699 fmol/DBS punch [ 37 ] collected at baseline and at specific study follow‐up visits [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation